(untitled) (مجلة ديالى للبحوث الانسانية, 2025)
Gothic is not a genre so easily defined. It tends more to be a mix of romance, fantasy, science fiction, and other discourses and patterns. It challenges the limits of society and explores the deep senses of horror and cruelty. On the other hand, Gothic brings a significant danger that culturally examines the morality of the society and psychological changes. Early, before the first wave of feminist literary history, the skill of writing gothic by women writers archived strong names that addressed human nature senses like fear as well as romantic elements and scientific concerns. The new alternatives that no longer repress female creative writings had put the subordination of women at the far side of the shelf and proposed a new wave of opposing sadly neglect of writing gothic by women. The power to redress the equilibrium and the participation of males and females in writing Gothic strongly hit the mix between realism and fantasy the moment they needed to explore their talent in writing. Currently, the appeal for re-focusing on women’s achievements in the gothic genre has encouraged academically researchers to investigate women’s understanding of horror and goth either as writers or as heroines. Thus, what the reader expects to read are lusty love, romance mixed with violence, revenge, wild passion, refusal of oppression, or vampire atmosphere. The paper discusses Gothic female writing as a developed genre with a reference historically to some prominent women writers until recent writings of some Gothicists. Arab female Gothic writers have a good share in depicting hard experiences such as war, death, and violence through Gothic references. The paper ends with a brief conclusion that summarizes how women radically use their weapons in writing Gothic to get their position of power.